2016
DOI: 10.4103/0253-7176.175105
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Treatment Setting by Substance Users in India

Abstract: Background:Drug and alcohol use is a growing public health concern for India. Treatment services delivery for substance use disorders is available through three sectors viz. Government (GO) centres under Ministry of Health and FW, Non-Government (NGO) under Ministry of Social Justice and Empowerment and the private sector. Information on ttreatment utilisation and preferences of treatment settings by substance users are not available for India.Methods:A performa was filled up prospectively for each consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…While preventing alcohol use in the population is crucial, it is also vital to provide appropriate health services to individuals with risky or harmful alcohol use to reduce the overall burden. The National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases and Stroke [61], the ‘Drug De‐addiction Programme’ [62] and a ‘Scheme for Prevention of Alcoholism and Substance (Drugs) Abuse’ [48]—all programs of the Government of India—are implemented throughout the country. These programs provide a range of services, including identifying individuals with alcohol use/harmful use and offering counselling, referral, treatment and rehabilitation.…”
Section: Alcohol Policies In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…While preventing alcohol use in the population is crucial, it is also vital to provide appropriate health services to individuals with risky or harmful alcohol use to reduce the overall burden. The National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases and Stroke [61], the ‘Drug De‐addiction Programme’ [62] and a ‘Scheme for Prevention of Alcoholism and Substance (Drugs) Abuse’ [48]—all programs of the Government of India—are implemented throughout the country. These programs provide a range of services, including identifying individuals with alcohol use/harmful use and offering counselling, referral, treatment and rehabilitation.…”
Section: Alcohol Policies In Indiamentioning
confidence: 99%
“…Alcohol has also been part of the NCD risk factor surveys, which are implemented at infrequent intervals in different states, providing information on prevalence, harm, type, frequency and quantity of alcohol consumed [152]. The ‘Drug Abuse Monitoring System’ tracks the pattern of alcohol use and profile of treatment seekers at government de‐addiction centres [62]. These examples by their very nature provide limited information on various aspects of alcohol use in the country.…”
Section: Alcohol Policies In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] It is estimated that currently, India has about 4 million people who use opioids and around 1 million people who are opioid dependent. [ 3 ] A recent study reported that around 232,000 people were opioid dependent in Punjab alone. [ 4 ] Thus, there is undoubtedly a sizable burden of opioid dependence in many parts of India.…”
Section: Introductionmentioning
confidence: 99%
“…Because the country is between the golden crescent (Iran, Afghanistan, and Pakistan) and the golden triangle (Myanmar, Thailand, Laos, and Vietnam), areas where much of the region’s opium is grown, northern India has increased access to heroin and other opioids. The result is a well-documented opioid epidemic to which researchers, government agencies, and nongovernmental organizations have been coordinating a response (Balhara, Gupta, & Lal, 2016; Basu, Gaur, Das, & Mattoo, 2011; Basu, Jhirwal, & Mattoo, 2005; Dayal, Balhara, & Mishra, 2016; De, Mattoo, & Basu, 2003; Dhawan, Chopra, & Ray, 2016; Dhawan, Pattanayak, Chopra, Tikoo, & Kumar, 2016; Government of India, Ministry of Home Affairs, & Narcotics Control Bureau, 2016; Joseph & Badyal, 2016; M. S. Kumar & Sharma, 2008; Singh et al, 2011; Vaswani & Desai, 2004).…”
mentioning
confidence: 99%